Assessment and Analysis of Sustainable Agroecosystem Management Through the Implementation of an Integrated Farming System (IFS) In Lempenge Hamlet, Rempek Village - Zainab, Zainab; Astiko, Wahyu (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Tropical drylands in Indonesia face serious challenges in maintaining food security due to limited water availability, soil degradation, and low production efficiency. This study aims to evaluate the potential application of an Integrated Farming System (IFS) integrated with the Internet of Things (IoT) as a model for sustainable agroecosystem management in Lempenge Hamlet, Rempek Village, North Lombok Regency. The research employed a case study approach through the analysis of primary literature, field observations, and national policy reviews related to agriculture and food security. The findings indicate that the major constraints in the agroecosystem include limited water resources, soil degradation, the dominance of monoculture systems, and the low socio-economic capacity and digital literacy among farmers. The implementation of IoT-based IFS demonstrates significant advantages, including a 15–50% increase in land productivity, up to 30% efficiency in water and fertilizer use, and a 17% reduction in carbon emissions through organic waste recycling and precision input management. Moreover, the model contributes to higher farmer income, enterprise diversification, and stronger village institutions. However, implementation remains limited by high investment costs, inadequate internet infrastructure, and insufficient technical skills among farmers. Therefore, policy support such as equipment subsidies, institutional strengthening, digital literacy training, and the use of low-power communication networks like LoRaWAN is required to promote adaptive and sustainable smart farming systems in Indonesia’s tropical dryland regions.